2021
DOI: 10.1080/21655979.2021.2003927
|View full text |Cite
|
Sign up to set email alerts
|

Apcin inhibits the growth and invasion of glioblastoma cells and improves glioma sensitivity to temozolomide

Abstract: Glioblastoma (GBM) is the most common malignant primary brain tumor, and GBM patients have a poor overall prognosis. CDC20 expression is increased in a variety of tumors and associated with temozolomide (TMZ) resistance in glioma cells. Apcin specifically binds to CDC20 to inhibit APC/C-CDC20 interaction and exhibits antitumor properties. The purpose of this article was to assess whether apcin inhibits tumor growth in glioma cell lines and increases the sensitivity of GBM to TMZ. In this study, a series of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The accumulation of evidence has demonstrated that CDC20 is dramatically elevated in human malignancies (including pancreatic cancer, breast cancer, and lung cancer), and CDC20 contributes to the malignant progression of cancer by degradation of its downstream target genes (such as CDKN1A (P21), Cyclin B1, and Bim) through ubiquitination, making it a promising target for cancer treatment [24]. In glioma, CDC20 has been identified as an oncogenic factor mediating tumor cell growth, invasion, and chemosensitivity [25]. Targeting CDC20 inhibits the malignant progression of glioma and CDC20 is considered an attractive target for therapeutic intervention [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of evidence has demonstrated that CDC20 is dramatically elevated in human malignancies (including pancreatic cancer, breast cancer, and lung cancer), and CDC20 contributes to the malignant progression of cancer by degradation of its downstream target genes (such as CDKN1A (P21), Cyclin B1, and Bim) through ubiquitination, making it a promising target for cancer treatment [24]. In glioma, CDC20 has been identified as an oncogenic factor mediating tumor cell growth, invasion, and chemosensitivity [25]. Targeting CDC20 inhibits the malignant progression of glioma and CDC20 is considered an attractive target for therapeutic intervention [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of CDC20 has been demonstrated in multiple cancer cell models including PCa by the compound Apcin (175)(176)(177). Mechanistically, it acts as an APC-CDC20 E3 ligase inhibitor, thus interfering with CDC20 binding to its substrates, causing a blockade of mitotic exit and consequently apoptosis.…”
Section: Cdc20mentioning
confidence: 99%
“…The accumulation of evidence has demonstrated that CDC20 is dramatically elevated in human malignancies (including pancreatic cancer, breast cancer, and lung cancer), and CDC20 contributes to the malignant progression of cancer by degradation of its downstream target genes (such as CDKN1A, Cyclin B1, and Bim) through ubiquitination, making it a promising target for cancer treatment [24]. In glioma, CDC20 has been identi ed as an oncogenic factor mediating tumor cell growth, invasion, and chemosensitivity [25]. Targeting CDC20 inhibits the malignant progression of glioma and CDC20 is considered an attractive target for therapeutic intervention [26,27].…”
Section: Introductionmentioning
confidence: 99%